ANALISIS INDEPENDENSI ODITUR MILITER DALAM MELAKSANAKAN FUNGSINYA DI ODITURAT MILITER III-14 DENPASAR DENGAN BERLAKUNYA KEBIJAKAN RENCANA TUNTUTAN - Misran Wahyudi (University of Udayana, 2015)
Military Prosecuting Attorney is one of the main components in enforcing the criminallaw in the military judicature system. Moreover, the Military Prosecuting Attorneys is asa prosecutor in the Indonesian National Armed Forces (TNI). Confidently, it has majorfunction in demanding based on legitimating evidences in military court. Military ProsecutingAttorney can work its duty well, if it has independently in the function as general presector ofIndonesian military court system. Afterwards, the first problem is wheter Military ProsecutingAttorney independently achieve its function in Oditurat Militer III-14 Denpasar by conductedthe plan demans policy as of Military Prosecuting Attorney General Indonesian NationalArmed Forces? Whereas, the second problem is whether the efforts shoud be accomplishedin establishing independent Military Prosecuting Attorney? This research was conducted byempirical legal research methods, and the study was a descriptive analytic research by usingprimary data and secondary data. Based on this research, it can be concluded that; first,Military Prosecuting Attorneys in Oditurat Militer III-14 Denpasar became less independent,it was occured because the implementation of the plan demand policy by Military ProsecutingGeneral Attorney. It can be stated that the demand was only established by upper position andfinally, the judgments are not merely according conscience. Secondly, Military ProsecutingAttorney attempt to independently in military justce system in three aspects such as technicalfield of prosecution, field supervision and control, as well as education and training.